КҮНХОЖА ШЫҒАРМАЛАРЫНЫҢ ТАРИЙХНАМАСЫ - Есназарова, З.Б. (FAN va JAMIYAT, 2023)
The article analyzes the historical aspects of Kunkhojas work, supplementing the informational and source content of events known in the Karakalpak history.